Liraglutide-induced injection site reaction - Nada Fouda Neel; Yasser Ghobara; Mohammed Turkmani (Wolters Kluwer Medknow Publications, 2019)
Liraglutide is an antidiabetic drug given subcutaneously for weight reduction. We report a 35-year-old woman who presented with a rash after starting liraglutide. The rash consisted of erythematous well-defined plaques surrounded by ecchymotic patches on extensor aspects of the thighs at the sites of liraglutide injection with gradual onset and progressive course. The exact cause of the reaction is unknown. The eruption resolved after discontinuation of treatment.